Targeting EMT in Cancer with Repurposed Metabolic Inhibitors - Ramesh, Vignesh; Brabletz, Thomas; Ceppi, Paolo (Trends in Cancer, 2020)
Epithelial-to-mesenchymal transition (EMT) determines the most lethal features of cancer, metastasis formation and chemoresistance, and therefore represents an attractive target in oncology. However, direct targeting of EMT effector molecules is, in most cases, pharmacologically challenging. Since emerging research has highlighted the distinct metabolic circuits involved in EMT, we propose the use of metabolism-specific inhibitors, FDA approved or under clinical trials, as a drug repurposing approach to target EMT in cancer. Metabolism-inhibiting drugs could be coupled with standard chemo- or immunotherapy to combat EMT-driven resistant and aggressive cancers.
CRIS-Team Scopus Importer:2020-07-24
Keywords: chemoresistance; drug repurposing; epithelial–mesenchymal transition; metabolic inhibitor; partial EMT